Influence of mean sea level rise on tidal dynamics of the Ria de Aveiro lagoon, Portugal - Lopes, Carina L.
Global mean sea level rise is an important consequence of climate change because of its impact on coastal regions. Recent studies highlight that tidal propagation in shallow waters tends to be modified with mean sea level rise, intensifying coastal threats. This study aims to quantify changes in tidal patterns in Ria de Aveiro coastal lagoon, Portugal in response to the local mean sea level rise. To achieve this goal the hydrodynamic model ELCIRC, previously calibrated and validated for Ria de Aveiro, was applied, considering the present mean sea level and a local mean sea level rise projection of 0.42 m for the end of the 21st century, assuming no change in bed elevation. The model results for present mean sea level show that the amplitude of the main semidiurnal (M2) and diurnal (K1) constituents decrease whereas the respective phase increases towards the head of the estuary, while the M4 constituent shows an opposite pattern, due to the upstream lagoon shallowness. As consequence, the tidal distortion is higher in the lagoon upper reaches than at the lagoon mouth. Under mean sea level rise conditions, the tidal wave tends to be less distorted in the upper lagoon, given that the M2 amplitude tends to increase while the M4 amplitude tends to decrease. The results highlight that tidal current magnitude decreases toward the channel’s head for both scenarios, but their magnitude tends to increase with mean sea level rise. The residual currents showed a net export of materials to the ocean, which will increase with mean sea level rise.